Accounting for Non-Accounting Students: Determinants and Academic Performance - Aliana Shazma Amir Binti Amir; Shafawaty Mohamad Shabri (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2022)
This study examines the determinants affecting the academic performance of non-accounting students in completing an accounting course, that is, Principles of Accounting. A secondary data was administered to a total of 497 non-accounting students who enrolled in a Principles of Accounting course for a semester. The factors considered are program, gender, race, background and lecturers which include deep, surface and strategic approaches on academic Performance by International Business and Engineering Entrepreneurship students at UniMAP. Motivational systems theory is used in this study which explains more on the initiation of learning strategies to do things, people’s behaviour and what directs or channels such behaviour is maintained or sustained. Using multiple regression analysis, the results reveal that program, gender, race, background and lecturers have a positive significant impact on academic performance by non-accounting students. This present study mainly focused on the overall performance of the students The findings imply that the Principles of Accounting course is relevant to be included in business course since it plays a vital role in running a business in the future regardless of program they are enrolling, gender, race, background and lecturers. Additionally, for as long as money has exited, so has accounting. Students can be well-disciplined in managing money, financial records and knowing the current economic condition of the country taking taxes as an example as to know the reputation and health of self-finance and country’s condition. The present study is unique as it considers the students’ performance in a subject that is not the main discipline of the students (i.e., accounting course for non-accounting students).